Examining the role of employability as a mediator in the relationship between psychological capital and objective career success amongst occupational psychology professionals - Elsey, Vicki; Van der Heijden, Beatrice; Smith, Michael A.; Moss, Mark (Frontiers in Psychology, 2022)
Employability is core to our understanding of career sustainability, and at an individual level, identifying the personal resources which support employability in the achievement of career success is warranted. This study builds on Conservation of Resources theory examining the role of employability as a mediator in the relationship between psychological capital and objective career success. To test our hypotheses we utilised a context-specific practitioner sample of 135 individuals, with UK-accredited Occupational Psychology qualifications. Employability was conceptualised using the competence-based model, underpinned by occupational expertise. Psychological capital and employability were measured using self-report questionnaires, while career success was determined via gross annual salary and practitioner status, ensuring objective measures of this outcome variable. Structural equation modelling identified that the relationship between psychological capital and objective career success was fully mediated by employability. These novel findings have important theoretical and practical implications for the role of psychological capital as a personal resource in achieving career success, via its influence on employability.